Abundant Expression of Guidance and Synaptogenic Molecules in the Injured Spinal Cord - Jacobi, Anne (Public Library of Science, 2014)
BACKGROUND: Spinal interneurons have emerged as crucial targets of supraspinal input during post-injury axonal remodelling. For example, lesioned corticospinal projections use propriospinal neurons as relay stations to form intraspinal detour circuits that circumvent the lesion site and contribute to functional recovery. While a number of the molecules that determine the formation of neuronal circuits in the developing nervous system have been identified, it is much less understood which of these cues are also expressed in the injured spinal cord and can thus guide growing collaterals and initiate synaptogenesis during circuit remodelling. METHODOLOGY/PRINCIPAL FINDINGS: To address this question we characterized the expression profile of a number of guidance and synaptogenic molecules in the cervical spinal cord of healthy and spinal cord-injured mice by in situ hybridization. To assign the expression of these molecules to distinct populations of interneurons we labeled short and long propriospinal neurons by retrograde tracing and glycinergic neurons using a transgenically expressed fluorescent protein. Interestingly, we found that most of the molecules studied including members of slit-, semaphorin-, synCAM-, neuroligin- and ephrin- families as well as their receptors are also present in the adult CNS. While many of these molecules were abundantly expressed in all interneurons examined, some molecules including slits, semaphorin 7a, synCAM4 and neuroligin 1 showed preferential expression in propriospinal interneurons. Overall the expression pattern of guidance and synaptogenic molecules in the cervical spinal cord appeared to be stable over time and was not substantially altered following a midthoracic spinal cord injury. CONCLUSIONS: Taken together, our study indicates that many of the guidance and synaptogenic cues that regulate neuronal circuit formation in development are also present in the adult CNS and therefore likely contribute to the remodelling of axonal connections in the injured spinal cord.